Mobile Financial Management Application at Yanto Pulsa Using Flutter - Naufal latiful Hakim; Ike Yunia Pasa (Universitas Mercu Buana Yogyakarta, 2026)
The utilization of digital technology in financial management has become an important need for micro, small, and medium enterprises (MSMEs) to improve recording accuracy and facilitate financial monitoring. However, many MSMEs still rely on manual financial recording, which may lead to recording errors and difficulties in data management. This study aimed to develop a mobile-based financial recording application as a solution for financial management at Yanto Pulsa. The system was developed using the Waterfall method, which consisted of requirement analysis, system design, application development, and testing stages. The application was built using the Flutter framework with Firebase as the backend and Cloud Firestore as the database. The results showed that the application was able to record income and expense data in real-time, present financial summaries, and support effective data management and backup. Black-box Testing results indicated that all application functions operated according to user requirements.